Pengaruh Rasio Keuangan Terhadap Financial Distress Dengan Profitabilitas Sebagai Variabel Moderating - Salma Salma; Wawan Ichwanudin (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2022)
The purpose of this study is to determine the effect of liquidity, leverage and sales growth on financial distress and to determine the role of profitability as a moderator between liquidity, leverage and sales growth on financial distress. The sample was selected using a purposive sampling technique, with a total sample of 11 coal sub-sector companies on the IDX. The analytical method used is moderated regression analysis (MRA). The results of this study indicate that liquidity has a significant positive effect on financial distress, leverage has a significant negative effect on financial distress, sales growth has an insignificant negative effect on financial distress. And profitability can weaken the effect of liquidity on financial distress, profitability can weaken the influence of leverage on financial distress, profitability cannot moderate the effect of sales growth on financial distress.